1994
DOI: 10.1148/radiology.191.3.8184058
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial polyps, hyperplasia, and carcinoma in postmenopausal women: differentiation with endovaginal sonography.

Abstract: Endovaginal sonography may be useful for differentiation of endometrial polyps, hyperplasia, and carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 0 publications
4
42
1
3
Order By: Relevance
“…Dilatation and curettage does not require an expensive apparatus and is a method available to most gynecologists, but it carries many risks, costs and limitations, such as the impossibili ty to obtain selected tissue samples, which leads to poor sensitivity as compared to hysteroscopy [11,12], Transvaginal sonography has been extensively used to evaluate postmenopausal bleeding [13,14] and the finding of cys tic spaces seeems to be predictive of endometrial polyps [15]. Although this is a useful tool for the presumptive diagnosis of endometrial lesions, it is not as accurate as hysteroscopy and the final diagnosis can only be made by biopsy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Dilatation and curettage does not require an expensive apparatus and is a method available to most gynecologists, but it carries many risks, costs and limitations, such as the impossibili ty to obtain selected tissue samples, which leads to poor sensitivity as compared to hysteroscopy [11,12], Transvaginal sonography has been extensively used to evaluate postmenopausal bleeding [13,14] and the finding of cys tic spaces seeems to be predictive of endometrial polyps [15]. Although this is a useful tool for the presumptive diagnosis of endometrial lesions, it is not as accurate as hysteroscopy and the final diagnosis can only be made by biopsy [16].…”
Section: Discussionmentioning
confidence: 99%
“…They are then supposed to be the cause of the abnormal bleeding, even though this is not necessarily the case [15]. The typical ultrasound appearance of a benign endometrial polyp is thick hyperechogenic endometrium with or without regular small cysts (cysts are common in atrophic polyps where the glands are cystically dilated [16]) and the presence of a "bright edge" [17,18] (Figure 6). The bright edge is explained by the interface between the polyp (or any other focal lesion in the uterine cavity) and the endometrium [1,18].…”
Section: Benign Endometrial Polypsmentioning
confidence: 99%
“…Other abnormalities, such as endometrial polyps and submucous fibroids, are difficult to diagnose by D&C. 22 In addition, many patients with PMB whose initial endometrial biopsy or D&C results reveal benign or insufficient tissue may eventually be diagnosed as having endometrial cancer or complex endometrial hyperplasia. 23 Numerous recent investigations [5][6][7][8][9][10][11] indicate that TVS is an effective procedure to exclude endometrial and intrauterine abnormalities, and advocate its use as a routine first-step procedure in patients with abnormal uterine bleeding. The prevalence of endometrial carcinoma is higher in women in whom the endometrium is thicker than 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] In these women, a thickening of the endometrium exceeding 5 mm indicates the presence of pathologic endometrial lesions (a sensitivity of 97% for detecting a carcinoma). [5][6][7][8][9][10] Biopsies of endometria of less than 5 mm thick are nearly always negative or result in tissue insufficient for diagnosis, 11 however, endometrial thickening is a nonspecific finding that can be due to hyperplasia, polyps, fibroids (intraluminal or submucosal), and carcinoma. 11 Several recent reports have indicated that transvaginal hysterosonography (TVHS) can improve the specificity of transvaginal sonography (TVS) in differentiating endoluminal masses from more diffuse endometrial thickening.…”
mentioning
confidence: 99%